Stress drives soccer athletes` wellness and movement: using convergent cross-mapping to identify causal relationships in a dynamic environment - Stern, B. D.; Deyle, E. R.; Hegedus, E. J.; Munch, S. B.; Saberski, E. (International Journal of Sports Physiology and Performance, 2024)
Purpose Prediction of athlete wellness is difficult—or, many sports-medicine practitioners and scientists would argue, impossible. Instead, one settles for correlational relationships of variables gathered at fixed moments in time. The issue may be an inherent mismatch between usual methods of data collection and analysis and the complex nature of the variables governing athlete wellness. Variables such as external load, stress, muscle soreness, and sleep quality may affect each other and wellness in a dynamic, nonlinear, way over time. In such an environment, traditional data-collection methods and statistics will fail to capture causal effects. If we are to move this area of sport science forward, a different approach is required.